A native, highly active Tc1/mariner transposon from zebrafish (ZB) offers an efficient genetic manipulation tool for vertebrates. Issue 4 (8th February 2021) - Shen, Dan; Song, Chengyi; Miskey, Csaba; Chan, Shuheng; Guan, Zhongxia; Sang, Yatong; Wang, Yali; Chen, Cai; Wang, Xiaoyan; Müller, Ferenc; Ivics, Zoltán; Gao, Bo
Abstract: New genetic tools and strategies are currently under development to facilitate functional genomics analyses. Here, we describe an active member of the Tc1/mariner transposon superfamily, named ZB, which invaded the zebrafish genome very recently. ZB exhibits high activity in vertebrate cells, in the range of those of the widely used transposons piggyBac ( PB ), Sleeping Beauty ( SB ) and Tol2 . ZB has a similar structural organization and target site sequence preference to SB, but a different integration profile with respect to genome-wide preference among mammalian functional annotation features. Namely, ZB displays a preference for integration into transcriptional regulatory regions of genes. Accordingly, we demonstrate the utility of ZB for enhancer trapping in zebrafish embryos and in the mouse germline. These results indicate that ZB may be a powerful tool for genetic manipulation in vertebrate model species.